Simple low-cost construction and calibration of accurate pneumotachographs for monitoring mechanical ventilation in low-resource settings - Farré, Ramon; Rodríguez-Lázaro, Miguel A.; Gozal, David; Trias, Gerard; Solana, Gorka; Navajas, Daniel; Otero, Jorge (Frontiers in Medicine, 2022)
Assessing tidal volume during mechanical ventilation is critical to improving gas exchange while avoiding ventilator-induced lung injury. Conventional flow and volume measurements are usually carried out by built-in pneumotachographs in the ventilator or by stand-alone flowmeters. Such flow/volume measurement devices are expensive and thus usually unaffordable in low-resource settings. Here, we aimed to design and test low-cost and technically-simple calibration and assembly pneumotachographs. The proposed pneumotachographs are made by manual perforation of a plate with a domestic drill. Their pressure-volume relationship is characterized by a quadratic equation with parameters that can be tailored by the number and diameter of the perforations. We show that the calibration parameters of the pneumotachographs can be measured through two maneuvers with a conventional resuscitation bag and by assessing the maneuver volumes with a cheap and straightforward water displacement setting. We assessed the performance of the simplified low-cost pneumotachographs to measure flow/volume during mechanical ventilation as carried out under typical conditions in low-resource settings, i.e. lacking gold standard expensive devices. Under realistic mechanical ventilation settings (pressure- and volume-control; 200 − 600 mL), inspiratory tidal volume was accurately measured (errors of 2.1% on average and < 4% in the worst case). In conclusion, a simple, low-cost procedure facilitates the construction of affordable and accurate pneumotachographs for monitoring mechanical ventilation in low- and middle-income countries.